Pengaruh Brand Image dan Sikap Konsumen Terhadap Ekuitas Merek Pada Produk Ija Kroeng di Kota Banda Aceh - Rahmi Rahmi; Nelly Nelly (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
Brand image and consumer attitudes  are important factors in influencing brand equity. Brand equity is the value of a brand, depend the extent to which the brand has high loyalty, the quality that is accepted by consumers and able to add more value to consumers. A strong brand equity can help a company in an effort to attract potential customers as well as efforts to establish good relationships with consumers and can eliminate consumer doubts about brand quality. This study was aimed to determine The Influence Of Brand Image And Consumer Attitudes Toward Brand Equity In Ija Kroeng Products In Banda Aceh. The sample of this study was 100 respondents. The data used in this study was quantitative data. The results showed that brand image and consumer attitudes had a significant effect on brand equity in Ija Kroeng products in Banda Aceh, it was proven by the brand image and attitude of consumers as factors that influence brand equity, which was proven by 84.9% of research results and the remaining 15.1 % explained by other variables outside of this research, for instance product quality, brand awareness, brand associations, etc. Statistical test results show  that simultan brand image and consumer attitudes have a significan effect on brand equity in Ija Kroeng products in Banda Aceh, Fcount>Ftable (272.719>3,090). While partially brand image and consumer attitudes have a significant effect on brand equity in Ija Kroeng products in Banda Aceh, with the value of tcount>ttable (11,871 and 2,051> 1,984). Based on the results of multiple linear regression  it can be seen that of the two variables that the brand image (X1) had the most dominant influence on brand equity in Ija Kroeng products in Banda Aceh, with a coefficient value of 0,805, and the followed by the variable attitudes of consumers (X2) with a coefficient value of 0,139.